News Editorial Strategy from Social Media as Online Media - Andi Nur Isman Sofyan; Yusmanizar Yusmanizar; Andi Vita Sukmarini (Journal La Bisecoman, 2024)
Online media continues to experience development both in terms of management to news content. This condition occurs along with the massive use of social media so that mass media often makes it one of the initial references in making a journalistic product. This research was carried out on detikcom media channel detikSulsel which also often broadcasts news of viral events from social media. The purpose of the study was to determine the strategy of detikcom detikSulsel channel in presenting viral news that references from social media so that the public avoid hoaxes. This study used descriptive qualitative method. In this case, researchers interpret and explain the data obtained from interviews, observations, and documentation, so as to get detailed and clear answers to problems. The results of the study found that detikcom editors of detikSulsel channel apply standards and strategies in presenting viral news from social media. detikcom media emphasizes professionalism and the Code of Journalistic Ethics in making news whose references are taken from social media. Among them, detikcom media is required to verify and interview if news references are taken from viral events from social media.